Green synthesis of cellulose/graphene oxide/ZIF8 derived highly conductivity integrated film electrode for supercapacitor. (15th November 2021) - Li, Jie; Sun, Ying; Kang, Weiwei; Wang, Pengna; Zhang, Huijun; Zhang, Xueqin; Yang, Hong; Lin, Baoping
Abstract: Natural polymer cellulose has been first employed to synthesize a thin (only 14.9 μm), lightweight (0.98 mg cm −2 ) and highly conductive (270.2 S cm −1 ) integrated film electrode by a green strategy in this report. Herein, cellulose nanofibers (CNFs) is planned as coordination modulation to develop zeolitic imidazolate frameworks (ZIF8s) with great morphology at room temperature. Particularly, the puzzle that monodispersed metal-organic frameworks (MOFs) are difficult to grow in aqueous solution is effectively solved. Moreover, the excellent film-formation and anisotropy of CNFs as well as the great mechanical properties of graphene oxide (GO) are exploited to constructed ingenious lamellar microstructure. Actually, the goal product carbonized-CNFs/GO/ZIF8 (CCGZ) with highly conductivity gets a "frame structure" belonging to architecture in part on the strength of the volume shrinkage of carbon material. Eventually, CCGZ with unique topology delivers a specific capacitance of 432.8 F g −1 at 5 mV s −1, and the all-solid-state device achieves a desirable energy density of 14.92 Wh kg −1 at 200 W kg −1 . These electrochemical properties are ahead of similar materials and devices. Consequently, this green method without any toxic solvents expands the application of natural carbon materials, which also highly propels the industrialization of film electrode with complex microstructure. Graphical abstract: Image 1 Highlights: A green and facile synthesis method is first explored to prepare composite film cellulose/graphene oxide/ZIF8 (CGZ). Monodispersed ZIF8 crystals are successfully synthesized in aqueous solution with the coordination modulation of CNFs. The integrated film electrode CCGZ with "frame structure" is only 14.9 μm. The carbon skeleton greatly improves the conductivity of CCGZ. This integrated film electrode CCGZ l possess highly conductivity of 270.2 S cm −1 . The elaborate topological structure grants CCGZ outstanding electrochemical properties with 423.8 F g −1 at 5 mV s −1 .